Computation of rainfall rates in typical monsoon cases by the semi-prognostic method (MAUSAM, 1989)
A semi-prognostic approach, i,e one time step prediction is used to compute rainfall rates in typical monsoon region by three versions based on Kuo's parameterization scheme, Rainfall rates are generally over predicted, One version which includes mesoscale moisture convergence parameter gives better prediction than other versions, Three categories are found, over-predicted, under-predicted and no computed rainfall, The possible  reasons for these categories are discussed.